1994
DOI: 10.1111/j.1365-2133.1994.tb08522.x
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells are one major source of interleukin-4 in atopic dermatitis

Abstract: Several reports have shown the presence of T-helper lymphocytes with Th2 characteristics in the skin lesions of atopic dermatitis (AD). However, Th2 cells themselves require an exogenous pulse of IL-4 to initiate their differentiation and synthesis of IL-4. As mast cells have recently been shown to contain IL-4, this finding prompted us to investigate IL-4 in mast cells of AD lesions, to determine if they might provide the IL-4 pulse needed by the Th2 cells. In this study, we measured IL-4 immunoreactivity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 28 publications
7
111
0
Order By: Relevance
“…Immunohistochemical analysis has shown that Th2-type cytokines, especially IL-4, are predominantly produced by mast cells and CD4 ϩ T cells in this chronic CH model (11). Consistent with this, mast cells are one of the major sources of IL-4 in lesional skin from patients with AD (37). Therefore, the results of this study suggest that L-selectin and ICAM-1 regulate IgE production indirectly by controlling mast cell accumulation at sites of inflammation.…”
Section: Figuresupporting
confidence: 70%
“…Immunohistochemical analysis has shown that Th2-type cytokines, especially IL-4, are predominantly produced by mast cells and CD4 ϩ T cells in this chronic CH model (11). Consistent with this, mast cells are one of the major sources of IL-4 in lesional skin from patients with AD (37). Therefore, the results of this study suggest that L-selectin and ICAM-1 regulate IgE production indirectly by controlling mast cell accumulation at sites of inflammation.…”
Section: Figuresupporting
confidence: 70%
“…Mitosis of mast cells has been observed in AD lesions (74), suggesting a pathophysiologic role for mast cells in this disease. Furthermore, it has been shown that mast cells may be an initial source of IL-4 in the lesions, a cytokine which may drive the lesional T cells in a Th2 direction (75). An increased number of tryptase-positive mast cells lacking anti-in¯ammatory chymase activity have been demonstrated in nonlesional skin of AD and nummular eczema (76), and may be linkable to the mast-cell tryptase proposed as a candidate gene for AD.…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…Mast cells may be a major source of Th2 cytokines in AD (16), and mast cell-derived mediators may inhibit antimicrobial peptide secretion (75). Thus, in theory, targeting mast cells may allow for a down-regulation of Th2 skewing (which would be beneficial for the course of allergic conditions) and for restoring Th1 cytokine and antimicrobial peptide patterns, which in turn would improve innate immunity.…”
Section: Mast Cells -A Switch Board Of Innate Immunity and Allergic Rmentioning
confidence: 99%
“…addition, mast cells are thought to contribute to the Th2 phenotype because 60% of them are IL-4 producers (16). Mast cells may also release substantial amounts of selective Th2 cytokines in response to IL-1 and the epithelial-derived cytokine thymic stromal lymphopoietin (TSLP), which is profoundly expressed by keratinocytes in atopic dermatitis.…”
mentioning
confidence: 99%